Simulation of Material and Heat Balance of 150 t AOD Melting 430 Stainless Steel under Different Charge Conditions - Lu Xiaohui, Kang Congpeng, Chen Hongzhi, Xu Yongbin (Teshugang)
In order to explore the influence of different charge conditions on the process of AOD smelting stainless steel， taking 430 stainless steel smelting in 150 t AOD furnace as an example， based on the actual production process， a material and heat balance simulation system of AOD refining stainless steel process was constructed. Through simulation calculation， the furnace temperature change under different charge conditions and related technical and economic indexes are deeply compared and analyzed.The results show that the furnace temperature will be low by using the raw material condition of dephosphorized molten iron and solid ferrochromium， and a large amount of ferrosilicon alloy should be added in the early stage of reduction to meet the requirements of steel tapping. Under this process condition， the consumption of ferrosilicon and lime reached 39.3 kg/t and 97.7 kg/t respectively， the continuous addition time of high carbon ferrochromium was about 12 min， the feeding rate was 4 t/min， and the maximum oxygen supply intensity at this time was 400 m3·min-1. By coordinating the relationship between oxygen supply and feeding rate， the temperature in the furnace was relatively stable； In the process of using dephosphorized molten iron + high chromium molten iron as furnace charge， the consumption of ferrosilicon and lime was 25.7 kg/t and 58.9 kg/t respectively. This process would generate heat surplus. By adding scrap steel as coolant to control the furnace temperature and meet the tapping temperature requirements， under this condition， the consumption of scrap steel per ton of steel was 169.1 kg， and the proportion of scrap steel added was 15.1%. The model calculation process can adjust and optimize the charge ratio according to the conditions of raw materials entering the furnace， which can provide theoretical and production guidance for AOD production of stainless steel.